Implementation of the GBI Bethany Tower of Christ Congregation Management Information System Design - Tanusaputra, Johan William; Ho, Abraham Cahyadi; Jeremy, Roger; Trisno, Indra Budi (Universitas Trilogi, 2024)
Along with the development of the digital era and pandemic conditions have increased the need for systems capable of working remotely. This motivated the researchers to conduct observations at the Bethany Tower of Christ Church. Based on observations and interviews that have been conducted with church pastors and deacons, it is found that the system already owned by the church has a lack of features, one of which is the feature of submitting requests to the church. In addition, there is also a need to update features related to adding devotionals, news, and posts to make it more practical and efficient. The development of this system uses the Waterfall method in which in the process the researcher first conducts direct observation and research at the Bethany Tower of Christ Church followed by analyzing the needs of the church and congregation which results in the design of a congregation management system. As for after the design is done, the system implementation is carried out. After that, researchers conducted testing of system maintenance. Based on the overall results obtained from the survey of respondents' assessment of the website, an average assessment of 87.3% was obtained, indicating that the website is feasible and has impressive respondent satisfaction. Researchers still find shortcomings in the system created, namely the lack of some features and the presence of bugs that need to be fixed. However, researchers still hope that the designed system can be useful for congregations and churches and can continue to be developed and maintained so that the system can be better.